2001
DOI: 10.1002/pola.10023
|View full text |Cite
|
Sign up to set email alerts
|

Gel formation in atom transfer radical polymerization of 2‐(N,N‐dimethylamino)ethyl methacrylate and ethylene glycol dimethacrylate

Abstract: Copolymers of 2‐(N,N‐dimethylamino)ethyl methacrylate (DMAEMA) and ethylene glycol dimethacrylate (EGDMA) were synthesized via atom transfer radical polymerization using ethyl 2‐bromoisobutyrate as the initiator, Cu(I)Br as the catalyst, and 1,1,4,7,10,10‐hexamethyltriethylene tetramine as the ligand. At low crosslinker levels, the polymerizations followed the first‐order kinetics. However, when the crosslinker level was above 10 mol %, the ln([M]0/[M]) versus time curves showed deceleration at medium conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
71
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 16 publications
5
71
1
Order By: Relevance
“…The cross-linking density 1 was calculated from the plot in Figure 10 and equals 0.026, which is very close to the value of 0.029 determined by Hunkeler et al [19] for PDMAEMA-based networks prepared by ATRP using ethylene glycol dimethacrylate as cross-linking agent. Notably, these values differ only by a factor of three compared to Florys equation (1 = 0.01), which is quite satisfying taking into account the difference of several orders of magnitude usually observed for conventional FRP.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The cross-linking density 1 was calculated from the plot in Figure 10 and equals 0.026, which is very close to the value of 0.029 determined by Hunkeler et al [19] for PDMAEMA-based networks prepared by ATRP using ethylene glycol dimethacrylate as cross-linking agent. Notably, these values differ only by a factor of three compared to Florys equation (1 = 0.01), which is quite satisfying taking into account the difference of several orders of magnitude usually observed for conventional FRP.…”
supporting
confidence: 84%
“…More recently, atom-transfer radical polymerization (ATRP) has also been used for the synthesis of cross-linked polymers. Jiang et al reported a one-step gelation process involving the ATRP of either N,N-dimethylamino-2-ethyl methacrylate (DMAEMA) with ethyleneglycol dimethacrylate (EGDMA) cross-linker, [19] or methyl methacrylate (MMA) with EGDMA [20] for which they evidenced an autoacceleration rate at high conversion due to diffusion-controlled radical deactivation. Zhu et al [21,22] demonstrated that ATRP leads to more homogeneous networks than those produced by FRP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the syntheses of crosslinked polymers with well-controlled network structures by controlled/living radical polymerization methods have been reported. [31][32][33] The mechanism and kinetics in a network forming ATRP system may be very different from those in linear and/or branching ATRP systems since the development of a threedimensional network restricts the mobility of reactive species such as monomers and catalyst/ligand complexes. From a fundamental viewpoint, our knowledge about the polymerization behavior and kinetics in network forming ATRP systems is severely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It would be desirable to have a synthetic route to synthesize homogeneous polymer networks using free radical technology. This goal may be achieved by copolymerizing vinyl and divinyl monomers in the presence of CLRP controllers [6].The production of polymer networks by controlled/living radical copolymerization (CLRC) techniques, including the copolymerization of vinyl/divinyl monomers, has already been addressed in the literature for the cases of INIFERTER [16][17][18][19], ATRP [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], NMRP [6,[37][38][39][40][41][42][43][44][45][46][47], and RAFT [48][49][50][51][52][53][54][55][56][57][58][59][60]. A short review of these studie...…”
mentioning
confidence: 99%